Creștinismul ortodox și ideologia totalitară - Czobor, Mihaela (Calitatea Vieții, 1994)
What the present paper aims at, is to analyse the social destiny of some Christian Orthodox ideas. This means to highlight the way these issues prepared the Romanian society to receive and embrace the totalitarian ideology and also the way these Christian Orthodox ideas furnished to the totalitarian ideology an already made structure for it, to implement.